2007
DOI: 10.1097/bcr.0b013e31802c8980
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Wound Contraction of Full-Thickness Skin Grafts are Associated With the Degree of Tissue Edema of the Graft Bed in Immediate Excision and Early Wound Excision and Grafting in a Rabbit Model

Abstract: The objective of this study was to evaluate the survival of skin grafts on graft beds of immediate excision and early wound excision at various time periods after burns and to establish the appropriate timing of burn excision and grafting in a rabbit model. Eight groups of male Japanese white rabbits (n = 5 per group) were established. Animals of all groups were given a 5 x 10-cm full-thickness burn on their shaved back and received the autografting 3, 6, 12, 18, 24, 48, and 72 hours and 5 days after receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…[1] Keratinocytes may also play a distinct role at the early stages of contraction, since studies have shown that keratinocytes are capable of inducing collagen gel contraction in vitro. [12][13][14][15] The actinfilament organization within keratinocytes at the wound margin appears to be responsible for the epidermal "purse-string phenomenon". [14] In addition, cytokines and growth factors such as ransforming growth factor-β1, insulin-like growth factor and fibroblast growth factors have also been found to play a major role in secondary contraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Keratinocytes may also play a distinct role at the early stages of contraction, since studies have shown that keratinocytes are capable of inducing collagen gel contraction in vitro. [12][13][14][15] The actinfilament organization within keratinocytes at the wound margin appears to be responsible for the epidermal "purse-string phenomenon". [14] In addition, cytokines and growth factors such as ransforming growth factor-β1, insulin-like growth factor and fibroblast growth factors have also been found to play a major role in secondary contraction.…”
Section: Discussionmentioning
confidence: 99%
“…[14] In addition, cytokines and growth factors such as ransforming growth factor-β1, insulin-like growth factor and fibroblast growth factors have also been found to play a major role in secondary contraction. [15] Unlike secondary contracture, which is the result of a prolonged biological process, primary skin graft contraction is mainly an immediate physical change in graft dimensions mediated by the tough fibrous layer of the dermis, which is primarily composed of collagens, glycosaminoglycans and elastins.…”
Section: Discussionmentioning
confidence: 99%
“…A treatment option that has helped to decrease mortality over the past 10 yrs has been the immediate excision of burned skin with replacement by grafted skin [2–4]. The ideal material for grafting is autologous skin, taken from a non‐burned region of the patient’s own skin.…”
Section: Introductionmentioning
confidence: 99%
“…The current standard of care for burns requiring operative treatment is early burn excision and split-thickness skin grafting (3, 4). Autologous skin, harvested from nonburned regions of the patient’s own body, is preferred; however, in large burns, sufficient donor sites may not be available to achieve the necessary coverage even when meshed grafts are utilized (5, 6).…”
mentioning
confidence: 99%